ANALISIS STRATEGI PENGEMBANGAN USAHA PETERNAKAN AYAM PETELUR DITINJAU DARI ASPEK MODAL DI KECAMATAN GEMPOL KABUPATEN PASURUAN JAWA TIMUR - Kenor, Benediktus; Humaidi, Faisol; Budiwan, Adi (Jurnal Agribisnis Wijaya Putra Surabaya, 2022)
This study aims to determine the costs and revenues of laying hens, internal and external factors that are strengths, weaknesses, opportunities and threats at UD Animal Husbandry Sumber Suko. The analytical method used to find out the weaknesses, strengths, opportunities and threats is a SWOT analysis. And to calculate the amount of business expenses and income using a calculator. From the analysis of the research results, it is known that the cost of laying hens at UD Sumber Suko is Rp. 3,387,052,600.00 per farming period and; the amount of income from laying hens at UD Sumber Suko is Rp. 5,640,420,000.00 per farming period and the income of laying hens at UD Sumber Suko is Rp.2.253,367,400.00. Alternative strategies that can be applied in an effort to develop a laying hens business at UD Sumber Suko are optimizing the potential of natural resources and sanitation of production inputs, labor, disease prevention supported by laying hens that are resistant to climate change.This study uses purposive sampling technique to obtain samples, and the number of samples taken. The population in this study at UD Sumber Suko Farm were all employees who were actively working at UD Sumber Suko Laying Chicken Farm, data collection using questionnaires. The results obtained that the selection of priority strategies at UD Sumber Suko Layer Chicken Farm is to increase market share, improve production quality, carry out effective and targeted promotions, and develop the quality of human resources